2019
DOI: 10.1002/celc.201900632
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Photoassisted Electrocatalytic Reduction of CO2 over a Two‐dimensional MoS2 Nanostructure Loaded on SnO2 Nanoparticles

Abstract: Photoelectrochemical reduction of CO2 to value‐added chemicals and fuels is an attractive strategy to store renewable energy and mitigate greenhouse gas emissions. In this study, based on the density functional theory (DFT) calculation, a two‐dimensional nanostructure MoS2 loaded on SnO2 nanoparticles (MS/SON) was prepared for photoassisted electrocatalytic reduction of CO2 to HCOOH through a two‐step process of facile hydrothermal and pyrolysis method. Through physical structure characterization and photoelec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…Hu et al examined the photo-assisted electrocatalytic reduction of CO 2 with 2D MoS 2 loaded onto SnO 2 nanoparticles, which are known to be selective toward HCOOH. 78 The study found that a 5% MoS 2 on SnO 2 was ideal for photocatalytic performance for the conversion of CO 2 to HCOOH with a current density of 9.8 mA cm −2 at −1.4 V vs Ag/AgCl and overpotential of 0.245 V vs RHE. The faradaic efficiency for the HCOOH product was also determined to be 43.8% at −0.85 V vs Ag/AgCl in aqueous 0.5 M NaHCO 3 buffer with a photocurrent value of 12.5 μA cm −2 , which implies that the SnO 2 nanoparticles aid in the selectivity and charge separation of the MoS 2 .…”
Section: Transition Metal Dichalcogenide Heterojunction Structures Fo...mentioning
confidence: 96%
See 1 more Smart Citation
“…Hu et al examined the photo-assisted electrocatalytic reduction of CO 2 with 2D MoS 2 loaded onto SnO 2 nanoparticles, which are known to be selective toward HCOOH. 78 The study found that a 5% MoS 2 on SnO 2 was ideal for photocatalytic performance for the conversion of CO 2 to HCOOH with a current density of 9.8 mA cm −2 at −1.4 V vs Ag/AgCl and overpotential of 0.245 V vs RHE. The faradaic efficiency for the HCOOH product was also determined to be 43.8% at −0.85 V vs Ag/AgCl in aqueous 0.5 M NaHCO 3 buffer with a photocurrent value of 12.5 μA cm −2 , which implies that the SnO 2 nanoparticles aid in the selectivity and charge separation of the MoS 2 .…”
Section: Transition Metal Dichalcogenide Heterojunction Structures Fo...mentioning
confidence: 96%
“…The faradaic efficiency for the HCOOH product was also determined to be 43.8% at −0.85 V vs Ag/AgCl in aqueous 0.5 M NaHCO 3 buffer with a photocurrent value of 12.5 μA cm −2 , which implies that the SnO 2 nanoparticles aid in the selectivity and charge separation of the MoS 2 . 78 Qiao et al studied a p-n heterojunction made with MoS 2 nanosheets and 1D SnO 2 fibers with a low molar ratio of Mo/Sn for use as a 4-nitrophenol reduction catalyst. 79 The heterostructure here showed excellent selectivity to the reduction of 4-nitrophenol with the increased activity being attributed to the hierarchical structure exposing more active sites of the catalyst as well as the p-n junction responsible for efficient charge separation.…”
Section: Transition Metal Dichalcogenide Heterojunction Structures Fo...mentioning
confidence: 99%
“…244 Hu et al investigated MoS 2 nanosheets loaded on SnO 2 nanoparticles as a photocathode. 245 It was discovered that a 5% loading of MoS 2 is the best for increasing the catalytic activity in terms of Faradaic efficiency and current density, with respect to the bare SnO 2 .…”
Section: Hydrogen Evolution Reactionmentioning
confidence: 99%
“…Several other oxides have been applied for PEC CO 2 RR such as Co 3 O 4 , [ 133,255 ] NiO 2 , [ 256 ] SnO 2 , [ 257 ] etc. Among them, Co 3 O 4 has striked as an appealing choice for oxide materials on account of its suitable bandgap ≈2 eV which spans in the visible range and its exceptionally high selectivity toward formate.…”
Section: Semiconductors As Photocathodesmentioning
confidence: 99%